"The stage of social evolution in which we find ourselves is already fused with artificial intelligence, far beyond any point of return". Interview with Dr. Martin Hilbert - Hilbert, Martin (2018)
Martin Hilbert is, without a doubt, one of the most outstanding researchers of recent times. From his multidisciplinary works published in scientific journals of great impact and trajectory, he has made it possible for us to understand the information society more completely. Hilbert has worked for different international organizations and is particularly interested in the role of information or big data in complex social systems. Disciple of Manuel Castells, and currently, he is an associate professor in the Communications Department of the University of California. With this interview, we wanted to delve into the way in which Hilbert sees the impact of digitalization in areas such as economics, research, politics, social sciences and humanity, in general.